2018
DOI: 10.22235/cp.v12i1.1591
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficacia y estilos de afrontamiento al estrés en estudiantes universitarios

Abstract: La presente investigación analizó la relación entre los niveles de Autoeficacia presentes en estudiantes universitarios y los Estilos de Afrontamiento al Estrés utilizados para hacer frente a demandas internas y externas. Se seleccionó una muestra de 126 estudiantes  a quienes se les administró la Escala de Autoeficacia General, el Cuestionario de Estilos de Afrontamiento al Estrés y un cuestionario sociodemográfico. Los resultados indican que quienes presentan un mayor nivel de Autoeficacia utilizan los Estil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 13 publications
1
11
0
26
Order By: Relevance
“…Positive coping skills and personal resilience are key factors that may protect an individual from lockdown-induced fatigue and other mental and psychological health consequences of the pandemic and the measures implemented to control the disease. Personal resilience is important for successful recovery from difficult or stressful circumstances (Hart, Brannan, & De Chesnay, 2014), while coping skills are helpful to resolve or hasten the resolution of a problem (Piergiovanni, & Depaula, 2018). In the context of a pandemic, adequate personal resilience and coping skills are vital to help an individual cope with the negative effects of the pandemic and support their mental health (Labrague & De los Santos, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Positive coping skills and personal resilience are key factors that may protect an individual from lockdown-induced fatigue and other mental and psychological health consequences of the pandemic and the measures implemented to control the disease. Personal resilience is important for successful recovery from difficult or stressful circumstances (Hart, Brannan, & De Chesnay, 2014), while coping skills are helpful to resolve or hasten the resolution of a problem (Piergiovanni, & Depaula, 2018). In the context of a pandemic, adequate personal resilience and coping skills are vital to help an individual cope with the negative effects of the pandemic and support their mental health (Labrague & De los Santos, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when certain situations or events exceed the individual’s own capacities, general self-efficacy decreases, and this may play an important role in stress generation. In these situations, coping strategies are needed to manage the high levels of stress (Piergiovanni and Depaula, 2018). Lazarus and Folkman (1984), in its model of coping with stress, conceptualized stress as the interaction between the person and his/her environment.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of one coping strategy or another may be determined by the level of self-efficacy perceived (Vandercleyen et al, 2014). Different studies have found an association between the perception of self-efficacy and the coping strategies employed (Vandercleyen et al, 2014; Zambianchi and Ricci-Bitti, 2014; Gárriz et al, 2015; Piergiovanni and Depaula, 2018); however, these have not included emotional continuum of individuals such as anxiety (in a positive sense) or emotional intelligence (in a negative sense) in the same model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations